An efficient, tunable, and robust source of narrow-band photon pairs at the 87Rb D1 line - Mottola, Roberto; Buser, Gianni; Mueller, Chris; Kroh, Tim; Ahlrichs, Andreas; Ramelow, Sven; Benson, Oliver; Treutlein, Philipp; Wolters, Janik (Optics Express, 2020)
We present an efficient and robust source of photons at the 87Rb D1-line (795 nm) with a narrow bandwidth of δ = 226(1) MHz. The source is based on non-degenerate, cavity-enhanced spontaneous parametric down-conversion in a monolithic optical parametric oscillator far below threshold. The setup allows for efficient coupling to single mode fibers. A heralding efficiency of ηheralded = 45(5) % is achieved, and the uncorrected number of detected photon pairs is 3.8 × 103/(s mW). For pair generation rates up to 5 × 105/s, the source emits heralded single photons with a normalized, heralded, second-order correlation function g( c 2) <0.01. The source is intrinsically stable due to the monolithic configuration. Frequency drifts are on the order of δ/20 per hour without active feedback on the emission frequency. We achieved fine-tuning of the source frequency within a range of >2 GHz by applying mechanical strain.
CRIS-Team Scopus Importer:2023-04-20